Pengaruh Kemampuan Intelektual, Emosional dan Spiritual terhadap Hasil Belajar PAI Siswa di SDN 15 Sutijo - Arif Aulia Rizki; Hidayani Syam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research was motivated by the relatively limited understanding of students in grades 3, 4 and 5 at SDN 15 Sutijo regarding PAI material. Many students have not demonstrated attitudes and behavior that reflect religious teachings well. Then, most students experience difficulties in achieving the expected competency standards in Islamic Religious Education subjects, including from the emotional and spiritual aspects of students. Many students lack motivation and feel anxious during the learning process, which has a negative impact on learning outcomes. Then some students also show apathy and lack motivation in taking religious lessons. This can be seen from the low average test scores and the results of observations of student interactions in class. So this research aims to determine the influence of IQ, EQ and SQ on students' PAI learning outcomes. This type of research is quantitative correlation. The population was 30 students and the sample used a total sampling technique. Data was collected through questionnaires and documentation and analyzed using simple and multiple linear regression tests. The research results show that IQ, EQ and S1 influence students' PAI learning outcomes. IQ has an effect of 14.4%, EQ of 14.3%, SQ of 27.2%. Then IQ, EQ and SQ together also influence students' PAI learning outcomes, namely 27.4% and the rest is influenced by other factors not examined in this research.